A Handbook of Costume Drawing: A Guide to Drawing The Period Figure For Costume Design Students - Baker (Georgia O daniel) ("17-A / 1, Main Ring RoadLajpat Nagar IV,New Delhi,New Delhi,India-110 024", 2007)
Fashion
22.5
Keywords: Fashion